Preoperative Serum Platelet-Lymphocyte Ratio as a Prognostic Factor in Cholangiocarcinoma Patients after Radical Resection: A Retrospective Analysis of 119 Patients. (28th January 2019) - Wu, Ying; Zhou, Danyang; Zhang, Guoping; Yi, Fengming; Feng, Long
Abstract : Aims . Although prognostic markers are important to establish therapeutic strategies in patients for conducting radical resection of cholangiocarcinoma (CCA), there is still a lack of simple, valid, and repeatable markers in clinical settings. We aim to evaluate the prognostic value of the preoperative serum platelet-lymphocyte ratio (PLR) in CCA patients who underwent radical resection. Methods . We retrospectively analyzed CCA patients who underwent radical resection surgery in our institution from January 2011 to June 2016. Baseline PLR and other clinical pathological data were measured when patients were diagnosed initially. The prognostic value of PLR in overall survival (OS) and progression-free survival (PFS) were analyzed with the Cox proportional hazard model and the Kaplan–Meier method. Results . This study retrospectively analyzed 119 patients who underwent radical resection of CCA. During a median follow-up time of 11.0 months, there were 99.2% recurrences and 42.9% who died, and the median OS and PFS were 9.4 months and 7.4 months, respectively. Multivariate Cox analysis identified that elevated levels of PLR (P L R > 157.25 ) as a significant factor predicted poorer OS (P = 0.018, HR: 2.160, 95% CI: 1.139-4.096) and PFS (P = 0.005, HR: 1.930, 95% CI: 1.220-3.053). In subgroup analysis, PLR also effectively predicted OS (P = 0.016, HR: 2.515, 95% CI: 1.143-5.532) and PFS (P = 0.042, HR: 1.908, 95% CI: 0.982-3.713) in CCA patients with positive lymphatic metastasis and/or positive surgical margin who required adjuvant therapy. Conclusions . The preoperative serum PLR is an independent prognostic factor for OS and PFS in CCA patients after radical resection, including patients requiring adjuvant therapy.